Innovation Management in Acceptance of New Students in State Senior High Schools in Indonesia - Leo B. Barus (Journal of Information System and Technology Issues, 2022)
The classic problems of Admission of New Students to Public High Schools in Indonesia still occurs, including extortion issue, disappointment of students' parents about zoning regulations, access to educational services issue, intervention by officials, registration difficulties, and lack of seat capacity. Those problems must be addressed due to the mandate of Article 31 of the 1945 Constitution of the Republic of Indonesia and the commitment of the state to the Sustainable Development Goals charter that has been mutually agreed upon with the United Nations. It was concluded that the handling was carried out through innovation management, namely through the use of certain technologies and applications that supposed to be designed innovatively according to the culture, nature and conditions of each regions in Indonesia. The technologies and applications must be accessible to the public through the website of the provincial education office or an online android application which must be designed by the provincial education offices in Indonesia.